Evaluation of the current situation of the Hungarian higher education based on a few indexes - Varga, Balázs; Vincze, Szilvia (Acta Agraria Debreceniensis, 2012)
Around the Millennium we experienced the worldwide development and the growing importance of the role of higher education played in the social and economic development. A few years later, however, a crisis appeared in the situation of higher education (Kadocsa, 2002). The Hungarian higher education system faces the perspective of serious changes in its fundamental principals – such as its main activities and the economical ways which are used to finance these activities – even if only parts of the new educational scheme come into effect. Considering this fundamental activity aspect of the issue, there are new challenges which make necessary to rethink the role and aim of higher education and to define the new tasks needed in connection with education, research and other services. Hungarian Education needs to be renewed and improved to avoid a completebreak away; therefore, future priorities and tasks in order to fulfill these priorities need to be defined (Vincze and Harsányi, 2011). The new conception seems to be based on restrictions of the budget as it is experienced recently: a new structure available for a smaller part of society with a restricted budget has been under development. However, not even a battle, let alone a war can be won without money, horses and arms. The recent financial restrictions as well as the parts of the Széll Kálmán plan concerning education prove that serious amounts of governmental funds is taken away from education. The international improvement tendencies contradict to basically all of these Hungarian priorities.All in all, no reform or change – no matter how much wanted – can be achieved without appropriate funds.